2006
DOI: 10.1103/physrevb.73.035110
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic ellipsometry study of optical anisotropy inGd5Si2Ge2and comparison with reflectance difference spectra

Abstract: The complex dielectric functions of single crystals of Gd 5 Si 2 Ge 2 were obtained using spectroscopic ellipsometry ͑SE͒ in the photon energy range of 1.5-5.0 eV at room temperature. Reflectance difference ͑RD͒ spectra for the a-b and b-c planes of single crystals of Gd 5 Si 2 Ge 2 were derived from these dielectric functions and compared to those obtained from reflectance difference spectroscopy ͑RDS͒ at near-normal incidence. The two experimental RD spectra from SE and RDS agreed well. The in-plane optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Later it was found that the silicide adopts the Gd 5 Si 4 -type structure. The variation of T C with pressure for Dy 5 Si 4 was found to be linear with dT C /dP equal to 3.0 K/GPa (Parviainen, 1980). The variation of T C with pressure for Dy 5 Si 4 was found to be linear with dT C /dP equal to 3.0 K/GPa (Parviainen, 1980).…”
Section: Dy 5 Si X Ge 4àxmentioning
confidence: 84%
See 2 more Smart Citations
“…Later it was found that the silicide adopts the Gd 5 Si 4 -type structure. The variation of T C with pressure for Dy 5 Si 4 was found to be linear with dT C /dP equal to 3.0 K/GPa (Parviainen, 1980). The variation of T C with pressure for Dy 5 Si 4 was found to be linear with dT C /dP equal to 3.0 K/GPa (Parviainen, 1980).…”
Section: Dy 5 Si X Ge 4àxmentioning
confidence: 84%
“…Formation of the Ho 5 Si 4 compound was investigated by Eremenko et al (1995), and it was reported that it forms by peritectic reaction L þ Ho 5 Si 3 ! The variation of T C with pressure for Ho 5 Si 4 was found to be linear with dT C /dP equal to 1.8 K/GPa (Parviainen, 1980). They reported a canted alignment of magnetic moments and a presence of two coexisting magnetic structures.…”
Section: Ho 5 Si X Ge 4àxmentioning
confidence: 93%
See 1 more Smart Citation